Pengaruh Kepemimpinan dan Kecerdasan Emosional Terhadap Kinerja Karyawan Pada Persahaan Umum Perumahan Nasional Regional 1 Medan Sumatera Utara - Misra Joviana Girsang; Hery Syahrial (Universitas Medan Area, 2021)
The purpose of this study was to determine whether leadership has a significant positive effect on employee performance at Perum Perumnas Regional 1 Medan, to determine whether Emotional Intelligence has a significant positive effect on employee performance at Perum Perumnas Regional 1 Medan and to determine whether leadership and emotional intelligence have a significant positive effect on employee performance at Perum Perumnas Regional 1 Medan. This type of research is associative, namely research to determine the effect of independent variables on the dependent variable, using multiple linear regression statistical analysis techniques. Then the research results obtained are leadership has a significant positive effect on employee performance with a value of 0.378 with a sig value of 0.000 smaller than the significant level of 0.05, emotional intelligence has a significant positive effect on employee performance with a value of 0.194 with a sig value of 0.047. small from the significant level of 0.05, then leadership and emotional intelligence have a significant positive effect on employee performance at the Regional Public Corporation of Perumnas 1 Medan, the value is 14.490 with a sig value of 0.001 smaller than the significant level of 0.05.